Time series investigation of changes in seasonality of acute diarrhea hospitalizations before and after rotavirus vaccine in Southern Brazil - Maria de Lourdes Teixeira Masukawa; Eniuce Menezes de Souza; Edilson Gimenes; Nelson Shozo Uchimura; Adriana Mayumi Moriwaki; Taqueco Teruya Uchimura
Abstract: Diarrhea by rotavirus is one of the main causes of mortality in children in developing countries, although the hospitalization rates (HR) for acute diarrhea have been found to have fallen since the introduction of the rotavirus vaccine. However, the patterns of the rotavirus are still not well understood and seasonal peaks occur throughout the year, with variations between countries and over time. The main objective of this study was to analyze the temporal behavior of HR caused by acute diarrhea in children under the age of one in the south of Brazil, between 2000 and 2011, and to explore changes in seasonality patters after the introduction of the vaccine against the rotavirus in 2006. Harmonic and multiscale wavelet analyses were used to detect seasonality and the points of change in the temporal scale. The statistical significance of each seasonality that was identified was tested using Fisher's test. The harmonic and wavelet analyses show annual seasonal and six-monthly patterns for HR, as well as a clear change after the introduction of the vaccine in 2006.